2017
DOI: 10.3348/kjr.2017.18.6.1005
|View full text |Cite
|
Sign up to set email alerts
|

Practice Pattern of Transthoracic Needle Biopsy: 2016 Survey in the Members of Korean Society of Thoracic Radiology

Abstract: ObjectiveTo assess the current practice patterns of radiologists who perform transthoracic needle biopsy (TNB).Materials and MethodsAn email survey of 71 questions on TNB was sent to 240 members of the Korean Society of Thoracic Radiology. The answers to multiple-choice questions (n = 56) were analyzed.ResultsOf 60 respondents, 45% had 10 or more years of experience in chest radiology, and 70% had 5 or more years of experience in TNB. For the question on the most frequently used diagnostic method for lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The number of repeated biopsies could have partially contributed to the increasing trend. According to a survey of Korean radiologists in 2016, the number of repeated biopsies increased over the past 5 years, and molecular analysis for an established target therapy and clinical trials of new drugs were identified as the main reasons [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of repeated biopsies could have partially contributed to the increasing trend. According to a survey of Korean radiologists in 2016, the number of repeated biopsies increased over the past 5 years, and molecular analysis for an established target therapy and clinical trials of new drugs were identified as the main reasons [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the 2003 BTS guideline remains the sole guideline dedicated to PTNB. Wide variations in domestic practice patterns of PTNB were reported among surveyed radiologists in Korea ( 7 ), the United States ( 8 ), and the United Kingdom ( 9 ). The lack of an up-to-date guideline for PTNB may be responsible for these variations in practice, potentially hampering the delivery of standardized diagnoses and management of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Blind bronchoscopic examination has a low success rate ( 12 ), whereas thoracic and thoracoscopic biopsies result in significant trauma in patients ( 13 , 14 ). For percutaneous transthoracic biopsy, although it remains the principal approach for the PPL diagnosis, it is less effective for lesions near the major vessels of the heart and diaphragm, in addition to those distant from the body surface ( 15 , 16 ); importantly, percutaneous transthoracic biopsy is performed through the non-natural lumina, leading to a high incidence of postoperative complications such as pneumothorax and bleeding ( 17 ). Hospitalization is therefore required for all patients undergoing percutaneous transthoracic biopsy, increasing the treatment cost and the use of medical resources ( 18 ).…”
Section: Discussionmentioning
confidence: 99%